A glutamate receptor-like gene is involved in ABA-mediated growth control in Physcomitrium (Physcomitrella) patens - Ya Wang; Dongsheng Yu; Hongmiao Zhao; Lanlan Jiang; Lei Gao; Yanan Song; Zebin Liu; Fang bao; Congcong Hou; Yikun He; Chuanli Ju; Legong Li; et al. (Plant Signaling & Behavior, 2022)
Plant glutamate receptor homologs (GLRs), which function as key calcium channels, play pivotal roles in various developmental processes as well as stress responses. The moss Physcomitrium patens, a representative of the earliest land plant lineage, possess multiple pathways of hormone signaling for coordinating growth and adaptation responses. However, it is not clear whether GLRs are connected to hormone-mediated growth control in the moss. In this study, we report that one of the two GLRs in P. patens, PpGLR1, involves in abscisic acid (ABA)-mediated growth regulation. ABA represses the growth of wild-type moss, and intriguingly, the PpGLR1 transcript levels are significantly increased in response to ABA treatment, based on both gene expression and the PpGLR1pro::GUS reporter results. Furthermore, the growth of Ppglr1 knockout moss mutants is hypersensitive to ABA treatment. These results suggest that PpGLR1 plays a critical role in ABA-mediated growth regulation, which provide useful information for our further investigation of the regulatory mechanism between Ca2+ signal and ABA in moss growth control.